Ethyl Pyruvate Prevents Methyglyoxal-Induced Retinal Vascular Injury in Rats. (28th February 2013) - Kim, Junghyun; Lee, Yun Mi; Kim, Chan-Sik; Sohn, Eunjin; Jo, Kyuhyung; Shin, So Dam; Kim, Jin Sook
Abstract : Pyruvate is an endogenous antioxidant substance. The aim of this study was to investigate the protective effects of ethyl pyruvate (EP) on retinal vascular injury in diabetic retinopathy. To investigate the protective effect of EP on vascular cell apoptosis and blood-retinal barrier (BRB) breakage, we have used intravitreally methylglyoxal-(MGO-) injected rat eyes. Apoptosis of the retinal vascular cell that was stimulated by the intravitreal injection of MGO was evidently attenuated by the EP treatment. EP exerts inhibitory effect on MGO-induced vascular cell apoptosis by blocking oxidative injury. In addition, EP treatment prevented MGO-induced BRB breakage and the degradation of occludin, an important tight junction protein. These observations suggest that EP acts through an antioxidant mechanism to protect against oxidative stress-induced apoptosis in retinal vessels.